The expression of VDACs and Bcl2 family genes in pituitary adenomas: clinical correlations and postsurgical outcomes - Facundo, AN; Magalhães, M; Nascimento, GC; Azulay, RS; Santos, RM; Freitas, LA; Nascimento, AGPAC; Rodrigues, VP; Santos, WC; Beckman, AMGS; Abreu, JMF; Silva, RP; et al. (Frontiers in Endocrinology, 2024)
Introduction: Pituitary adenomas (PAs) are benign tumors with high prevalence and, occasionally, aggressive course. The tumorigenesis of these lesions is not completely understood at the molecular level. BAK1 and BAX proteins play fundamental roles in apoptosis and seem to interact with VDAC proteins, whose expressions have been markedly altered in cancer, impacting their prognosis. Objective: to evaluate the gene expression of VDAC1, VDAC2, BAK1 and BAX and their association with clinical and imaging characteristics in PA. Methods: Clinicalepidemiological data were collected from 117 tumor samples from patients affected by PA.Invasiveness was assessed by the Knosp scale. Gene expression was examined by real-time PCR.Relative expression analysis was performed by 2^(-DDCt) method. Results: The sample was mainly composed of women (69/117 -57.2%). Tumor subtypes observed were Non-Functioning (NF) (73/117 -62.4%), Acromegaly (24/117 -20.5%) and Cushing's Disease (CD) (20/117 -17.1%). Compared to normal tissue, there was a significant reduction in VDAC1 expression in the Acromegaly (p=0.029) and NF (p=0.002) groups. BAX expression was lower in all groups (p <0.001; p=0.007; P =0.005). No difference was found in VDAC2 and BAK1 expression, compared to normal pituitary. Overexpression of VDAC2 occurred in PAs with post-surgical regrowth (p=0.042). A strongly negative correlation was observed in BAX and BAK1 expression in CD.The results indicated that downregulations of VDAC1 and BAX may be related to resistance to apoptosis. In contrast, overexpression of VDAC2 in regrowing PAs suggests an antiapoptotic role for this gene. In summary, the genes evaluated might be involved in the biopathology of PAs.